ANALISIS LAJU PERTUMBUHAN ANTARA KONTRIBUSI PAJAK HOTEL DAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KOTA BALIKPAPAN - Bravo Yengky Karundeng; Yudea Yudea (Fakultas Ekonomi Universitas Pekalongan, 2016)
This research aims to know the contribution and the rate of growth of hotel tax and restaurant tax tolocal revenue Balikpapan city. This research was conducted at the Department of Revenue office in thecity of Balikpapan. By using data analysis with quantitative descriptive way, the research concludedthat the realization of local revenue of hotel tax and restaurant tax in the years 2009-2013 was achieved. Tax receipts for contributions hotel tax and restaurant tax on local taxes in the year 2009 2013was not achieved, while the contribution receipts tax on hotel and restaurant tax to local revenuein the year 2009-2013 was not achieved. Therefore, the growth rate of hotel tax and restaurant tax fluctuate, the impact of not achieving the target of tax revenue.Keywords: Hotel Tax, Restaurant Tax, Rate of Growth, Local Revenue.